Prevalensi obesitas dengan menggunakan metode waist-hip ratio pada mahasiswa Program Studi Pendidikan Dokter Fakultas Kedokteran Universitas Udayana angkatan 2014 - Merlynda Ayu Rara Dini; I Gusti Ayu Widianti; I Nyoman Gede Wardana (Department of Anatomy, Medical Faculty, Universitas Udayana, Bali-Indonesia, 2018)
Nowadays, obesity is an endemic health problem almost all countries in the world are facing. Obesity itself is not a contagious disease and it actually can be avoided. Obesity happens because there is an abnormal fats accumulation and this abnormality can bring various negative effects for the body and its health. Waist Hip Ration (WHR) method can be used to decide whether or not a person has obesity, especially central obesity. This research aims to find out the prevalence of obesity using WHR method on the students of Medical Education Program in Medical Faculty of Udayana University (PSPD FK Unud) class of 2014. This research is a descriptive research with cross sectional research design. This research was done to 217 students, 77 male students (35,5%) and 140 female students (64,5%). The obesity was measured by measuring waist size and hip circumference, the ratio then will be determined by dividing waist size with hip circumference. Normally, WHR on men is <0,9 and <0,8 on women. The result of this research reveals that 58 students (26,7%), consisting of 27 male students (12,5%) and 31 female students (14,5%) have central obesity.